Self-tuning system for multistandard active RC filters. (August 2019) - Kladovščikov, Leonid; Navickas, Romualdas; Kiela, Karolis
Abstract: In this paper a new self-tuning system for active-RC filter with tunable bandwidth is presented. This self-tuning system compensates PVT inducted parameter drift for precise cut-off frequency, phase shift and output gain tuning. Low pass 2nd order active-RC filter with tunable bandwidth from 5 MHz to 40 MHz is designed and simulated using 0.18 μm CMOS technology. The self-tuning range and tuning step do not decrease below 25% and 0.8% respectively in the whole filter bandwidth selection range. Such a filter self-tuning system can be effectively used with modern wireless data transmission standards, such as LTE, WiMAX, WiFi to account for PVT induced mismatches in band selection filters.